Influence of Navier-slip conditions on natural convection flow through an inclined channel with inclined magnetic field, Soret and Hall current effects. (10th May 2021) - Kaladhar, Kolla; Reddy, K. Madhusudhan; Srinivasacharya, D.
This research is to examine the laminar, incompressible fluid with an inclined magnetic field on free convective Navier-slip flow through an inclined channel. In addition, the Hall current and Soret effects have also been considered. Dimensionless governing equations are derived by using the suitable transformations and the resulting governing partial differential equations are solved by using the spectral quasilinearisation method (SQLM). The influence of the flow parameters of the present study is explained in graphs. Physical quantities of the present study are shown in tabular form.